A profile of the belief in Jesus and salvation among the Afrikaans speaking Christian youth - Pieterse, Hendrik J. C. (HTS teologiese studies, 2003)
This article is based on the results of a large-scale empirical-theolo-gical research project on “Religion and Human Rights among South African Youth.” Using the extensive database of this project, the article focuses on the results on the images of Jesus and the belief in salvation of Grade 11 learners. The results present a profile of the pluralistic and diverse scale of nuances in the belief structures of Christian teenagers. The results of the English-speaking private school learners are placed alongside the results of the Afrikaans speaking public school learners in order to obtain a more prolific picture of the belief of the Afrikaans speaking youth. The effect their belief in salvation has on their views regarding human rights is also examined. The results challenge the preacher to think dialectically and hermeneutically in a new age and context.